Munc13 binds and recruits SNAP25 to chaperone SNARE complex assembly. Issue 3 (5th December 2020) - Kalyana Sundaram, Ramalingam Venkat; Jin, Huaizhou; Li, Feng; Shu, Tong; Coleman, Jeff; Yang, Jie; Pincet, Frederic; Zhang, Yongli; Rothman, James E.; Krishnakumar, Shyam S.
Abstract : Synaptic vesicle fusion is mediated by SNARE proteins—VAMP2 on the vesicle and Syntaxin‐1/SNAP25 on the presynaptic membrane. Chaperones Munc18‐1 and Munc13‐1 cooperatively catalyze SNARE assembly via an intermediate 'template' complex containing Syntaxin‐1 and VAMP2. How SNAP25 enters this reaction remains a mystery. Here, we report that Munc13‐1 recruits SNAP25 to initiate the ternary SNARE complex assembly by direct binding, as judged by bulk FRET spectroscopy and single‐molecule optical tweezer studies. Detailed structure–function analyses show that the binding is mediated by the Munc13‐1 MUN domain and is specific for the SNAP25 'linker' region that connects the two SNARE motifs. Consequently, freely diffusing SNAP25 molecules on phospholipid bilayers are concentrated and bound in ~ 1 : 1 stoichiometry by the self‐assembled Munc13‐1 nanoclusters. Abstract :